ANALISIS KEPUTUSAN PEMBELIAN PRODUK â€œLELONGâ€ PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS TANJUNGPURA - Nurhanida, Nurhanida; Witarsa, Witarsa; Budiman, Jumardi; Okianna, Okianna; Kuswanti, Heni (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
One of the products that students are interested in today is the products of imported used goods that are often referred to as "shell". The study is aimed at analyzing the purchasing decisions of retail products in FKIP University of Tanjungpura Economic Education Students. Research approach using qualitative and case study research methods. The data source used is the primary source. The sampling technique uses Purposive Sampling where samples are selected based on specific considerations. The informants of this study are students of economics education force 2019 - 2021 who have purchased clothing products at auction at least 3 times. Data collection techniques are interviews, literature, and observation. Data analysis methods include data reduction, data presentation, conclusion withdrawal. The results show that the basic aspects of consumer behavior are the cultural aspects due to foreign fashion; the social aspects are the products of clothing auctions presented by close relatives; the psychological aspects with a simple, fashionable and economical lifestyle. While the dimension of consideration of the purchase decision is the selection of products with detail in terms of quality and price; the choice of different brands has different quality characteristics of materials and models; complete store / location and friendly service; time of purchase without planned, make a purchase when looking at a good auction product; the number of purchases vary with the amount of purchase between Rs5,000-Rp200,000.